P565 Infliximab therapy intensification upon loss of response: what should be the cut-off for trough levels?. (25th January 2019) - Ungar, B; Ben-Shatach, Z; Ben-Haim, G; Yavzori, M; Picard, O; Fudim, E; Kopylov, U; Del Tedesco, É; Veyrard, P; Stephane, P; Eliaklim, R; Ben-Horin, S; et al.
Abstract: Background: Loss of response (LOR) to infliximab occurs in approximately 30% of IBD patients. At time of LOR, lower infliximab trough levels (TL), in the absence of anti-drug antibodies (ATI), have been associated with the need for therapy escalation. TL of 3–7 μg/ml have been defined as a clinical therapeutic window. Nevertheless, few studies have examined the outcome of infliximab-therapy intensification based on TL and ATI. Hence, our aim was to evaluate the impact of TL on therapeutic efficacy of dose intensification in IBD patients experiencing LOR to infliximab in the absence of ATI. Methods: This was a retrospective observational study of IBD patients receiving scheduled infliximab therapy at two tertiary centres between 2013–2017. Only patients who received infliximab dose intensification upon LOR after induction period were included. ATI positive patients were excluded. TL and clinical scores before therapy intensification and after 6, 12 months were obtained prospectively. The main outcome was clinical remission. Receiver-operating-characteristic-analysis was performed for TL using clinical remission as a classification variable. Results: Forty-eight IBD patients (31, 64% Crohn's patients) were included in the study; 23 (49%), 29 (60%) reached clinical remission by 6, 12 months of scheduled infliximab therapy. TL below 4.8 μg/ml before dose intensification were best associated with clinical remission, both at 6 (AUC=0.77, p = 0.0001, 91% sensitivity, 56% specificity) and 12 months (AUC=0.74, p = 0.001, 83% sensitivity, 53% specificity). Conclusions: In IBD patients experiencing LOR to infliximab in the absence of ATI, infliximab dose intensification is significantly more effective when pre-escalation TL are below 4.8 μg/ml. Thus, dose escalation is probably unlikely to be successful when TL are above 4.8 μg/ml.